Reliability and Validity of Gaze-Dependent Functional Vision Space: A Novel Metric Quantifying Visual Function in Infantile Nystagmus Syndrome - Roberts, Tawna L. (Invest Ophthalmol Vis Sci, 2018)
PURPOSE: This study presents test–retest reliability of optotype visual acuity (OVA) across 60° of horizontal gaze position in patients with infantile nystagmus syndrome (INS). Also, the validity of the metric gaze-dependent functional vision space (GDFVS) is shown in patients with INS. METHODS: In experiment 1, OVA was measured twice in seven horizontal gaze positions from 30° left to right in 10° steps in 20 subjects with INS and 14 without INS. Test–retest reliability was assessed using intraclass correlation coefficient (ICC) in each gaze. OVA area under the curve (AUC) was calculated with horizontal eye position on the x-axis, and logMAR visual acuity on the y-axis and then converted to GDFVS. In experiment 2, validity of GDFVS was determined over 40° horizontal gaze by applying the 95% limits of agreement from experiment 1 to pre- and post-treatment GDFVS values from 85 patients with INS. RESULTS: In experiment 1, test–retest reliability for OVA was high (ICC ≥ 0.88) as the difference in test–retest was on average less than 0.1 logMAR in each gaze position. In experiment 2, as a group, INS subjects had a significant increase (P < 0.001) in the size of their GDFVS that exceeded the 95% limits of agreement found during test–retest. CONCLUSIONS: OVA is a reliable measure in INS patients across 60° of horizontal gaze position. GDFVS is a valid clinical method to be used to quantify OVA as a function of eye position in INS patients. This method captures the dynamic nature of OVA in INS patients and may be a valuable measure to quantify visual function patients with INS, particularly in quantifying change as part of clinical studies.